Guidance in Model-based Compilations - Smyth, Steven; Schulz-Rosengarten, Alexander; von Hanxleden, Reinhard (Electronic Communications of the EASST, 2020)
The modeler should not be burdened with maintaining an overview over all potential conflicts. They should further be able to understand what is happening. Model-based compilers and modeling tools in general should guide a modeler. The KIELER Compiler constructs transformation snapshots and augmented models automatically during compilation. We demonstrate six different transient views that can help the modeler to refine their models and to solve modeling issues, such as causality problems in synchronous languages.